The social construction and control of medical errors: a new frontier for medical/managerial relations? - Waring, Justin J. (2004)
This thesis explores changes in medical professional work and regulation in the context of emerging 'patient safety' health policies. The study engages with three components of this policy. First, to what extent is the concept of error promoted in theory and policy being taken up within managerial practice and is this coterminous with the medical interpretation and construction of error? Second, how do medical professionals regard the introduction of new reporting systems to collect information about errors in their work? Third, what new organisational systems are being developed to analyse and control errors and how do these diverge with those approaches advocated and practiced by medical professionals? It has been estimated that one in ten of all inpatient admissions experience some form of error in the delivery of care, totalling 850,000 events a year. Given such findings a new policy framework is being developed to improve 'patient safety' in the NHS. Following the Human Factors approach a new error management system is being introduced that consists of incident reporting procedures for the collection of information about errors, matched by techniques to identify the "root causes", and promote organisational change. Of importance for this thesis is the impact of policy on established forms of medical regulation. Through predominantly qualitative research techniques, this study has been carried out within a single NHS hospital case-study involving medical and managerial occupational groups. The empirical findings suggest, firstly, that the medical construction of error is indeed divergent from that advocated in policy and practiced in management and leads to distinct trajectories for the control of error. Secondly, medical professionals are generally disinclined to participate in managerial forms of incident reporting, and where such a system is in place there is a high degree of localised professional leadership. Thirdly, it was found that alongside new managerial systems for the control of errors, there were also a range of professional-led systems embedded within medical work and the local organisation of the hospital that had precedence of other centralised hospital systems. In consequence, the ability of managerial systems to penetrate the working environment of medicine was negligible. In conclusion, it is argued that while this policy could appear to challenge the basis of medical professional regulation the social, cultural and structural context of medical work is adapting to maintain a high degree of medical control and resist managerial encroachment.